Associations between pigments, antioxidant activity and coloring of blackberry fruits (Rubus sp.) and jellies through storage - de Souza, Angela Vacaro [UNESP]; Putti, Fernando Ferrari [UNESP]; Vieira, Marcos Ribeiro da Silva; Vieites, Rogério Lopes [UNESP] (My University, 2019)
The objective of this study was to investigate the relations between the amount of anthocyanins, carotenoids and the antioxidant activity measured by the FRAP and TEAC methods. Furthermore, pigments and the coloration of blackberry harvested fruits were measured at 3 different collection points then fruits stored in refrigerated environment and the jelly made from them, preserved in hermetically sealed glasses, without contact with light and temperature of 25°C. In order to investigate the relations between the study variables (content of anthocyanins and carotenoids, antioxidant activity and coloration using digital colorimeter), Pearson's correlation analysis was adopted, which indicates the existence of a positive or negative relation between two variables. The a = 5% (correlation coefficient) was used to verify the significance of the correlation. The Mahalanobis (D2) generalized distance for the clustering analysis by the mean linkage method between group of blackberry fruits and jellies was applied. Furthermore, the cophenetic correlation coefficient and multivariate analysis using major components were applied to verify the grouping of different responses of harvesting points of fresh blackberry fruit in natura and jellies. The results showed that there was correlation between the content of anthocyanins and carotenoids in fruits (0.99*) and between the same parameters in jellies. However, this behavior was not clearly observed between the pigments and the antioxidant activity. There was a positive correlation between the factors involved in the coloring of chroma fruits 'L', 'a', 'b' and °Hue in fruits and jellies. Blackberry jellies presented as good sources of anthocyanins and carotenoids.
Keywords: Food processing; Harvest point; Multivariate analysis; Postharvest; Refrigerated storage; Rubus sp